An imaging K-band survey - I: The catalogue, star and galaxy counts - Glazebrook, K; Peacock, J; Collins, C; Miller, L (1993)
We present results from a large area (552\,\sqamin) imaging $K$-band survey to a 5$σ$ limit of $K\simeq 17.3$. We have optical-infrared colours of almost all the objects in the sample. Star-galaxy discrimination is performed and the results used to derive the infrared star and galaxy counts. $K$-band ``no-evolution'' galaxy-count models are constructed and compared with the observed data. In the infrared, there is no counterpart for the large excess of faint galaxies over the no-evolution model seen in optical counts. However, we show that the $K$ counts can be remarkably insensitive to evolution under certain reasonable assumptions. Finally, model predictions for $K$-selected redshift surveys are derived.